Effect of atomic hydrogen exposure on hydrogenated amorphous carbon thin films. (22nd November 2021) - Haruyama, Yuichi; Morimoto, Daiki; Heya, Akira; Sumitomo, Koji; Ito, Seigo; Yokota, Kumiko; Tagawa, Masahito
Abstract: The effect of atomic hydrogen exposure on hydrogenated amorphous carbon (a-C:H) films was investigated by X-ray photoelectron spectroscopy (XPS). From the dependence of the wide-scan XPS spectra of an a-C:H film on atomic hydrogen exposure, it was shown that the film was etched with an etching rate of 0.2 nm min −1 . In addition, by analyzing the C 1s XPS spectra, the coordination of C atoms in the a-C:H film was investigated as a function of the atomic hydrogen exposure and photoelectron emission angle. This indicated that the coordination of C atoms at the surface of the a-C:H film was not influenced by atomic hydrogen exposure. Therefore, we propose that the depth profile of a-C:H films can be measured with no damage using atomic hydrogen etching.